Late-onset alopecia areata: descriptive analysis of 30 cases - Rosana Lazzarini; Camila Bilac Oliari; Ana Luisa Nasser Erthal (Sociedade Brasileira de Dermatologia, 2016)
Abstract Alopecia areata is an autoimmune disease characterized by non-scaring hair loss. The onset in over 50-year-old patients is rare and has barely been studied. Cases of this disease have been retrospectively analyzed - according to clinical forms, extension, and associated diseases - to assess alopecia areata characteristics in a group of patients whose disease onset was after the age of 50. 30 patients were studied; a few of them presented with autoimmune-related diseases or family history. The disease onset after the age of 50 seems to have different characteristics from those found in young people.